2021
DOI: 10.1111/trf.16756
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and first‐in‐human clinical dose‐escalation safety evaluation of a next‐gen human freeze‐dried plasma

Abstract: Background: Early plasma transfusion is life-saving for bleeding trauma patients. Freeze-dried plasma (FDP) provides unique formulation advantages for infusion in the prehospital setting. We describe characterization and clinical safety data of the first, next-generation FDP stored in plastic bags with rapid reconstitution. Study design and methods: Coagulation and chemistry parameters on 155 pairs of fresh frozen plasma (FFP) and their derivative FDP units were compared. Next, a first-in-human, dose-escalatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…In the ensuing decades, FDP use has waxed and waned. Two papers in this issue of Transfusion illustrate the rising interest in the transfusion community in providing freeze‐dried plasma as a modern, sterile, readily reconstituted blood component in rugged plastic bags, initially for prehospital use in remote or austere environments 2,3 …”
mentioning
confidence: 99%
“…In the ensuing decades, FDP use has waxed and waned. Two papers in this issue of Transfusion illustrate the rising interest in the transfusion community in providing freeze‐dried plasma as a modern, sterile, readily reconstituted blood component in rugged plastic bags, initially for prehospital use in remote or austere environments 2,3 …”
mentioning
confidence: 99%
“…6 Cancelas et al showed firstin-human safety of FDP stored in plastic bags. 7 Additionally, comparable coagulation factor activity between frozen and freeze-dried solvent/detergent-treated plasma was demonstrated. FDP does not require thawing and could be an advantageous alternative to FFP.…”
Section: Covid-19 Convalescent Plasmamentioning
confidence: 90%
“…Sheffield and colleagues demonstrated retention of hemostatic and immunological properties of FDP and CCP 6 . Cancelas et al showed first‐in‐human safety of FDP stored in plastic bags 7 . Additionally, comparable coagulation factor activity between frozen and freeze‐dried solvent/detergent‐treated plasma was demonstrated.…”
Section: Blood Component Therapymentioning
confidence: 99%
“…More advanced in its development, the results of the first in-human use of a next-generation single-donor, nonpathogen reduced, FDP product manufactured by Teleflex Inc (Maple Grove, MN), have recently become available. Teleflex's FDP is stored in a rugged plastic IV bag container which permits reconstitution in one minute or less for immediate infusion and transport to far forward military settings [51 ▪▪ ]. No significant differences in the outcome of subjects undergoing autologous transfusion of up to 810 mL of FDP were identified compared with the same amount of FFP in a crossover design, and no serious adverse events were found after the infusions of any dose of FDP on study in healthy volunteers.…”
Section: Next-generation Lyophilized Plasma Productsmentioning
confidence: 99%
“…The coagulation factor activities and clotting times for pairs of prelyophilization FFP and postlyophilization Teleflex's FDP derived from apheresis citric acid-citrate-dextrose (ACD) or whole blood citrate-phosphate-dextrose (CPD) collection were found to be generally similar with preservation of coagulation factor activities and clotting times in the postlyophilized product. Cold-stored CPD FDP and ACD FDP had a slight prolongation of mean clotting times (prothombin time -PT-, international normalized ratio -INR-, activated partial thromboplastin time -aPTT-, and thrombin time -TT-) and minimal or modest reductions in the mean content of fibrinogen, factors II, V, VII, VIII, IX, X, XI, XII, Protein C, Protein S, plasmin inhibitor, plasminogen, antithrombin III, von Willebrand Factor (vWF) activity, and vWF antigen, compared to the FFP control [51 ▪▪ ], but all of them were well within the margin of 20% defined for bioequivalence by the US FDA [52], and with differences similar to those ones reported for the licensed PF24 and PF24RT24 plasma products [53]. For the Teleflex's FDP, the nonactivated partial thromboplastin time was always higher than 60 s (> 60 s) and the level of FVIIa was always lower than 105 mU/mL for CPD FDP and ACD FDP, indicating that the FDP manufacturing process did not result in relevant clotting activation of either the intrinsic or extrinsic pathways, further supporting the safety of this product.…”
Section: Next-generation Lyophilized Plasma Productsmentioning
confidence: 99%